Amalan Bersesuaian Perkembangan Dalam Pengurusan Bilik Darjah Prasekolah - Mohamad Jaafar, Anis Norma (2019)
Ineffectiveness of classroom management is one of the factors that causes the educational goals unachievable and that, interferes in children’s holistic development. Teachers’ understanding on the principles of children Developmentally Appropriate Practice (DAP) is crucial in ensuring the classroom management becoming more effective and conducive. This study aims to examine the extension of understanding and real practices of preschool teachers in applying the DAP into classroom management. In addition, this study looks at the coordination between understanding and practice in implementing the DAP into classroom management and further identifying the challenges faced in the implementation. This study focuses on the four dimensions of classroom management which consist of (a) the dimensions of management on physical classroom environment, (b) the dimensions of management on activity planning, (c) the dimensions of management on relationship and communication, and (d) the dimensions of management on children’s behaviour. This study is a case study using qualitative approach. Data collection was collected through semi structured interviews, observation and document analysis. A total of four preschool teachers from Sekolah Kebangsaan in Muallim, Perak Darul Ridzuan were samples for this study. Studies have found that teachers have a comprehensive understanding on the four dimensions of classroom management based on the children developmentally appropriate practice. However, the findings indicate that there is an inconsistency between teachers' understanding and their practice in managing the preschool classrooms